2022
DOI: 10.1177/08830738221089740
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Targeted Treatment Translation in Fragile X Syndrome as a Model for Neurodevelopmental Disorders

Abstract: Fragile X syndrome (FXS), the most common monogenic cause of intellectual disability and autism spectrum disorder, has been one of the first neurodevelopmental disorders in which molecular and neuronal mechanisms of disease were identified, leading to the concept of targeting the underlying disease to reverse symptoms. Translating findings in basic science and animal models to humans with FXS has proven difficult. These challenges have prompted the FXS field to organize to build interlocking projects and initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Such human neural models may be helpful in predicting translatability of new disease-directed agents in FXS. Even with such studies, it is likely to be very difficult to predict which pathways and treatment targets will translate well to individuals affected by the disorder, so early phase target engagement studies with objective measures in FXS participants are particularly important before moving to large trials that may use participant, time, and monetary resources to no positive end ( 11 , 38 , 39 ). Also, it will be imperative to measure animal model phenotypes that can be directly translated into humans, such as electrophysiological measures (EEG) and other biomarkers applicable to both mouse and human studies in FXS ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such human neural models may be helpful in predicting translatability of new disease-directed agents in FXS. Even with such studies, it is likely to be very difficult to predict which pathways and treatment targets will translate well to individuals affected by the disorder, so early phase target engagement studies with objective measures in FXS participants are particularly important before moving to large trials that may use participant, time, and monetary resources to no positive end ( 11 , 38 , 39 ). Also, it will be imperative to measure animal model phenotypes that can be directly translated into humans, such as electrophysiological measures (EEG) and other biomarkers applicable to both mouse and human studies in FXS ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant mRNA translation represents one of the major hallmarks of FXS and, therefore, a putative therapeutic target [2,14,119]. While therapies aimed at rescuing protein synthesis have provided successful results in mice [120], similar approaches have failed in clinical trials, highlighting the difficulties of translating data obtained in murine models to the clinic [4,5,43,44,66,121].…”
Section: Discussionmentioning
confidence: 99%
“…The Updated Report on tools to measure outcomes of clinical trials in FXS published in 2017 by an expanded 2013 Working Groups found that most outcome measures had limited information on its psychometric properties and lacked objective measures, particularly in the behavioral domain, which indicated that endpoint development in FXS needed to continue with an emphasis on objective measures [ 1 ]. The data provided here address the lack of objective data (directly observable or/and direct testing, quantifiable, biomarkers) to fill the gap in the endpoints and perhaps of the brain function in FXS, including to capture meaningful improvements in quality of life of individuals and families with FXS [ 1 , 2 ]. Specifically, the articles that contributed to that effort included here are on: (1) a comprehensive FMR1 genotype-protein-FXS phenotype profiles evaluation (Budimirovic et al); (2) psychometric properties of an adaptive functioning measure (Cordeiro et al); (3) delineating repetitive behavior profiles in FXS with and without ASD across the lifespan (Reisinger et al); (4) a potential direct measure of social interaction skills in individuals with FXS (Cordeiro et al); (5) validity of existing standardized and new promising sensitive to treatment of language-related assessments in FXS (two articles: 5a Shaffer et al and 5b Hoffmann et al); (6) correlates to health-related quality of life in FXS (Coffman et al); (7) a meta-analysis of the response to placebo in FXS controlled trials (Luu et al); and (8) a further analysis of a computer-based cognitive Cogmed FXS controlled trial data (Scott et al).…”
mentioning
confidence: 99%
“…In conclusion, we anticipate that the wide range of data published in this Special Issue will result in new and/or improved strategies that can be applied in FXS clinical trials and potential reduction in heterogeneity issues across FXS cohorts. The published data aim to address the gaps and limitations in knowledge related to objective outcome measures for successful clinical trials in FXS [ 1 , 2 ]. Despite tangible progress overall [ 2 ], translating the preclinical successes of the targeted interventions into clinical trials of humans in FXS still remains a challenge, and still no regulatory agencies have approved treatment in FXS.…”
mentioning
confidence: 99%
See 1 more Smart Citation